Structural Validity of the Pittsburgh Sleep Quality Index in Chinese Undergraduate Students - Guo, Suran; Sun, Wenmei; Liu, Chang; Wu, Siwei (Frontiers in Psychology, 2016)
The purpose of this study was to examine the structural validity of the Pittsburgh Sleep Quality Index (PSQI) in Chinese undergraduate students. A cross-sectional questionnaire survey with 631 Chinese undergraduate students was conducted, and the questionnaire package included a measure of demographic characteristics, Pittsburgh Sleep Quality Index (PSQI), Chinese editions of Center for Epidemiologic Studies-Depression, State- Trait Anxiety Inventory, Rumination Response Scale, and Perceived Social Support Scale. Results showed that the item “use of sleep medicine” was not suitable for use with this population, that a two-factor model provided the best fit to the data as assessed through confirmatory factor analysis, and that other indices were consistently correlated with the sleep quality but not the sleep efficiency factor.